Worldwide Research Productivity on Biosimilars: A Bibliometric Analysis - Hernández-Vasquez, A. (2017)
ABSTRACT objeCtives: Evaluation of worldwide scientific output on biosimilars has not been explored. Therefore, the objective of this study was to perform a bibliometric overview of global research productivity on biosimilars. Methods: An electronic search for original articles was conducted using the Web of Science database, with the term “biosimilar”. Bibliometric indicators were investigated by analyzing annual research output, languages, countries, journals, authors, institutions, citations, and funding agencies. Results: Bibliographic research retrieved 501 papers for the period 2005-2016. The yearly quantitative distributions of articles were highly correlated (R2= 0.88). The mostly used languages were English (475 articles), French (12 articles) and German (7 articles). Retrieved documents were published by 63 different countries. The largest contributors in absolute number of articles are the USA (160), Germany (75), and England (51). The articles were published in 140 journals. The top three journals which published the most of the biosimilars articles were Biodrugs, Mabs, and Biopharm International, responsible for 12% of the publication. The total number of authors for all articles was 2525. Chow, S.C. published the most documents in this field (14 articles), followed by Abraham, I. (8 articles), and Fareed, J., MacDonald, K., Rathore, A.S., and Schellenkens, H., all with six articles. A total of 19 articles were from Duke University, 18 corresponded to Amgen, Hexal AG and Pfizer, both with 12. The sum of the citations relates to articles published was 3332. Average citations per item were 6.65. Finally, Sandoz (33) and Pfizer (27) were the two major funding agencies of publications. ConClusions: In summary, biosimilars have been a hot topic in the last decade. Biosimilar therapies may help to reduce the healthcare costs with similar clinical outcomes, thereby more research is needed.